Clinical Application and Educational Training for Pharmacogenomics - Jason W. Guy; Isha Patel; Julie H. Oestreich (MDPI AG, 2020)
Pharmacogenomics-defined as the study of how genes affect a person's response to drugs-is growing in importance for clinical care. Many medications have evidence and drug labeling related to pharmacogenomics and patient care. New evidence supports the use of pharmacogenomics in clinical settings, and genetic testing may optimize medication selection and dosing. Despite these advantages, the integration of pharmacogenomics into clinical decisions remains variable and challenging in certain practice settings. To ensure consistent application across settings, sufficient education amongst current and future healthcare providers is necessary to further integrate pharmacogenomics into routine clinical practice. This review highlights current evidence supporting clinical application of medications with pharmacogenomic labeling. The secondary objective is to review current strategies for educating health professionals and student trainees. One national organization predicts that most regions in the United States will soon contain at least one healthcare system capable of applying pharmacogenomic information. Applying genotype-guided dosing to several FDA-approved medications may help produce beneficial changes in patient outcomes. Identifying best practices for educating health care professionals and trainees remains vitally important for continuing growth of pharmacogenomic services. As pharmacogenomics continues to expand into more areas of healthcare, current and future practitioners must pursue and maintain competence in pharmacogenomics to ensure better outcomes for patients.